Literacy and Research-Oriented Problem-Based Learning: Exploration of Implementation in Classroom Learning - Pratama, Faiz Ilham; Rohaeti, Eli; Laksono, Endang Widjajanti; Apriliana, Apriliana (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
Literacy and Research-Oriented Cooperative Problem-Based Learning (LIRACLE) is a new learning model developed for learning in higher education. LIRACLE is developed from a combination of problem-based learning, cooperative learning, research-oriented learning, and literacy-oriented learning. To complete the development of the LIRACLE model, a test of the implementation of the LIRACLE model is needed. The survey was conducted by asking for an assessment from two lecturers of the molecular dynamics course. The research was conducted for one semester. The instrument used was an observation sheet for the implementation of learning. The results of this study are the level of implementation of learning which is in the excellent category (E). This is because the systematic preparation of LIRACLE, accordance with the development of graduate skills, increases student enthusiasm, and has a clear basis for implementation. Therefore, the LIRACLE learning model can be said to have met the implementation test. This research is preliminary in the future development of the LIRACLE learning model